Pengaruh Kecepatan Putar Pengadukan dan Waktu Pendiaman Terhadap Rendemen dan Kualitas Minyak Kelapa Murni (VCO) - Arniah Dali; La Harimu La Harimu; LM. Cinong Simbiti (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2015)
It as done a research on the influence of the rotational speed of stirring and standing time on the yield and quality virgin coconut oil (VCO). VCO is made with mechanical engineering variations stirring round and standing time. Variations in the rotational speed of stirring cream coconut milk is 372, 385, 449, 503, and 539 rpm. The results were obtained optimum rotational speed is 503 rpm with a yield 23.66 % (v/v). Variations coconut cream standing time is 6, 7, 8, 9, and 10 hours. The results were obtained optimum standing time is 8 hours with a yield of 22.90 % (v/v), the water content of 0.17 %, acid content of 0.26 %, saponification value of 247.656 mg KOH/g of fat, and a peroxide value of 0.199 mL eq/kg.